Dracula agnosia (Orchidaceae: Pleurothallidinae), a long confused undescribed species - Doucette, Alfonso (Phytotaxa, 2012)
Dracula agnosia, long confused with D. olmosii, is formally described. The two species may be easily distinguished by their sepal morphology.